4(x-1)+6=2x-5(1+x)

Simple and best practice solution for 4(x-1)+6=2x-5(1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)+6=2x-5(1+x) equation:


Simplifying
4(x + -1) + 6 = 2x + -5(1 + x)

Reorder the terms:
4(-1 + x) + 6 = 2x + -5(1 + x)
(-1 * 4 + x * 4) + 6 = 2x + -5(1 + x)
(-4 + 4x) + 6 = 2x + -5(1 + x)

Reorder the terms:
-4 + 6 + 4x = 2x + -5(1 + x)

Combine like terms: -4 + 6 = 2
2 + 4x = 2x + -5(1 + x)
2 + 4x = 2x + (1 * -5 + x * -5)
2 + 4x = 2x + (-5 + -5x)

Reorder the terms:
2 + 4x = -5 + 2x + -5x

Combine like terms: 2x + -5x = -3x
2 + 4x = -5 + -3x

Solving
2 + 4x = -5 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
2 + 4x + 3x = -5 + -3x + 3x

Combine like terms: 4x + 3x = 7x
2 + 7x = -5 + -3x + 3x

Combine like terms: -3x + 3x = 0
2 + 7x = -5 + 0
2 + 7x = -5

Add '-2' to each side of the equation.
2 + -2 + 7x = -5 + -2

Combine like terms: 2 + -2 = 0
0 + 7x = -5 + -2
7x = -5 + -2

Combine like terms: -5 + -2 = -7
7x = -7

Divide each side by '7'.
x = -1

Simplifying
x = -1

See similar equations:

| -3x+3+7x=-13 | | 2/3x-5=20 | | 11y-1=5.75 | | (1/3)(27) | | 2.49(n+1.24)=11.17 | | 10y+10+5x=180 | | -2-2/3=12 | | 4.23-7.2x=3.6x-9 | | -2(3x+5)+4x=4 | | -12+4x=7x+17 | | -100(m-80)=4 | | (2x-5)+(4x+6)= | | 9x+44=9x-44 | | 6*-4+24= | | 6x+12y=288 | | 4=5x+3-5x | | -12790+185t=0 | | 82=2x-6 | | 4=5x+3+5x | | 2.5-8(1-5a)=-20.5 | | 4-6y=13 | | 3y-3x=-6 | | -8(3f+9)=18-5f | | -6s-5-2.5s=18.5 | | 8y+17=137 | | X-4.2=8.02 | | 27.5=-4+3(b+6.5) | | X+2.09=5 | | 0.7x=4.9 | | 7x+34=180 | | -n/18=-3 | | 2lm(x-3)=1 |

Equations solver categories